Pengaruh Independensi Dewan Komisaris, Komite Audit, dan Internal Audit Terhadap Fee Audit Eksternal (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2012-2014) - Wiliasti, Arlinia; , Noer Sasongko, SE, M.Si, Ak (2017)
This study aims to provide empirical evidence of influence: Good Corporate Governance factorsm(the Independence Board of Commissioners, the Independence Audit Committee, the Size of Audit Committee, the Meeting Intensity of Audit Committee, and Internal Audit) for the External Audit Fees on the company's Manufacturing registered BEI in 2012-2014. This Study was conducted using secondary data. The population in this study were 30 companies listed on the BEI during the period 2012-2014. The analytical method used is multiple linear regression analysis by first doing a description of the data, a classic assumption test including normality test, multicollinearity test, heterocedasticity test, autocorrelation test, and hypothesis testing are used is partial significance test (Uji-t), significant test simultaneous (Uji-F), and adjusted R Square. The result of this study prove that variable independence board of commissioners and the internal audit function did influence the external audit fees, while variable independence audit committee, size of audit committee, meeting intensity of audit committee did not influence the external audit fees.